SPSS statistics for dummies - McCormick, Keith; Salcedo, Jesus; Poh, Aaron (--For dummies, 2015)
"If you work in a field that uses SPSS Statistics, you may have found it overwhelming. The authors of this guide get you up and running and how you how to get the most from your data."--Resumé vydavatele